Bending of Responsive Hydrogel Sheets Guided by Field‐Assembled Microparticle Endoskeleton Structures. Issue 17 (10th March 2016) - Morales, Daniel; Bharti, Bhuvnesh; Dickey, Michael D.; Velev, Orlin D.
Abstract : Hydrogel composites that respond to stimuli can form the basis of new classes of biomimetic actuators and soft robotic components. Common latex microspheres can be assembled and patterned by AC electric fields within a soft thermoresponsive hydrogel. The field‐oriented particle chains act as endoskeletal structures, which guide the macroscopic bending pattern of the actuators.